MULTAQA TSAQAFI AS A MEDIUM FOR STRENGTHENING ARABIC LANGUAGE COMPETENCE AMONG FIFTH-GRADE KMI STUDENTS AT PONDOK MODERN DARUSSALAM GONTOR PUTRI 1 - Fairuz Subakir; Siti Nikmatul Rochma; Nuraeni Rahmawati; Nur Fera Khalifah (STKIP Pesisir Selatan, 2026)
This study investigates the role of Multaqa Tsaqafi in strengthening Arabic language competence among fifth-grade KMI students at Pondok Modern Darussalam Gontor Putri 1. Employing a qualitative case study design, the research explores how the program contributes to students' communicative competence, language habituation, and academic participation within the pesantren environment. Data were collected through participant observation, semi-structured interviews, and documentation analysis involving students, teachers, and language supervisors. The findings reveal that Multaqa Tsaqafi significantly strengthens students' Arabic communicative competence through contextual interaction, scientific discussion, and authentic language practice. The activity also reinforces the Arabic linguistic environment (bi'ah lughawiyyah) by encouraging continuous Arabic use in both academic and daily communication. Furthermore, the program promotes students' confidence, active participation, linguistic discipline, and academic motivation. Another important finding indicates that Multaqa Tsaqafi integrates language learning with Islamic character formation by cultivating communication ethics, intellectual responsibility, and discipline within pesantren culture.